Design & development of street light monitoring and management system - Mohd. Mokji, Musa (Universiti Teknologi Malaysia, 2007)
The management of streetlights by the power utility company and local authorities are typically faced with the problem of high operational expenditure, low efficiency and increase customer complaint. They are also faced with increase customer complaint due to unattended faulty streets lights and frequent power outages. There is a significant pressure to reduce these operational expenses, improve efficiency and image. By operational efficiency we meant how faulty street lights are managed effectively through the use of a low cost automated system, thus improve efficiency and enhancing customer services. Operational cost reduction is achieved through accurately identification of faulty lights and timely action taken to rectify such fault. Currently these maintenance routines [i.e. random patrols around the street light zones] are conducted daily in parallel to records of faulty lights reported by customers. These incurred substantially high operational expenditure year to year. The objective of this project is to develop a low cost SLM system with features suffice enough for the utility companies to effectively manage and maintain street lights and also monitor power quality to ensure continuous and uninterrupted supply to customers both residential and industries. SLMS consist of interface modules (FC-Feeder Controller, FIU-Feeder Interface Units) installed at the substation or streetlights panel to collect the status of power over each feeder pillar. Information of faulty lights collected by the FIU (which will measure the current/power on the feeder and record any changes e.g. a drop in power indicating a faulty light in that feeder line) is passed back to FC using the PLC (Power line carrier) technique. The FC manages several feeder pillars and relay back the information received from FIU to a management system server located at the office (RCC-Regional Control Center & NCCNational Control Center) using GSM network. RCC then sends an alert SMS to operational personnel to inform them of the faulty record. The management system keeps records for management reporting and analysis.